Characterization of new cell line stably expressing CHI3L1 oncogene - Balynska, O.V.; Baklaushev, V.P.; Areshkov, P.O.; Avdieiev, S.S.; Boyko, O.I.; Chekhonin, V.P.; Kavsan, V.M. (Вiopolymers and Cell, 2011)
Aim. To characterize the immortalized 293 cell line afterstable transfection with human oncogene (CHI3L1). Methods. 293 cells, stably transfected with pcDNA3.1_CHI3L1, and 293 cells, stably transfected with pcDNA3.1 as a negative control, were used throughout all experiments. The clones of CHI3L1-expressing 293 cells and 293 cells, transfected with pcDNA3.1, were analyzed by immunofluorescence and confocal microscopy. Cell proliferation was measured using MTT assay; analyses of ERK1/2 and AKT activation and their cellular localization were performed with anti-phospho-ERK and anti-phospho-AKT antibodies. Specific activation of MAP and PI3 kinases was measured by densitometric analysis of Western-blot signals. Results. The obtained results show quite modest ability of CHI3L1 to stimulate cell growth and reflect rather an improved cellular plating efficiency of the 293 cells stably transfected with pcDNA3.1_CHI3L1 as compared to the 293 cells transfected with an «empty» vector. ERK1/2 and AKT are activated in the 293_CHI3L1 cells. In these cells phosphorylated ERK1/2 were localized in both cell cytoplasm and nuclei while AKT only in cytoplasm. The 293_CHI3L1 cells differed from the 293 cells, transfected with an «empty» vector, in their size and ability to adhere to the culture plates. Conclusions. The overexpression of CHI3L1 is likely to have an important role in tumorigenesis via a mechanism which involves activation of PI3K and ERK1/2 pathways. The tumors which can be induced by orthotopic implantation of the transformed human cells with overexpressed human oncogene CHI3L1 into the rat brain can be used as a target for anticancer drug development. Key words: chitinase 3-like 1 protein (CHI3L1), brain tumor, MAP kinase, PI3 kinase. Мета. Охарактеризувати імморталізовану клітинну лінію 293 після стабільної трансфекції онкогена CHI3L1. Методи. Клітини 293, стабільно трансфековані pcDNA3.1_CHI3L1, та клітини 293, стабільно трансфековані pcDNA3.1 як негативний контроль, використано в усіх експериментах. Клони 293 експресуючих CHI3L1 клітин та клітини 293, трансфековані «порожнім» вектором, проаналізовано методами імунофлуоресценції та конфокальної мікроскопії. Клітинну проліферацію визначено за допомогою MTT, активацію ERK1/2 i AKT та їxню локалізацію в клітинax – із застосуванням анти-фосфо-ERK- та анти-фосфо-AKT-антитіл. Специфічну активацію кіназ MAP і PI3 визначено денситометричним аналізом Вестерн-блот сигналів. Результати. Отримані результати демонструють помірну здатність CHI3L1 стимулювати клітинний ріст, алe відображають скоріше підвищену здатність до прикріплення 293 клітин, стабільно трансфекованих pcDNA3.1_CHI3L1 порівняно з клітинами 293, трансфекованими «порожнім» вектором. У 293_ CHI3L1 клітинах ERK1/2 та AKT перебувають в активованому стані. У цих клітинах фосфорильованi ERK1/2 локалізованi як у цитоплазмі, так і в ядрі, тоді як AKT – лише в цитоплазмі. 293_CHI3L1-клітини відрізняються від клітин 293_pcDNA3.1 за морфологією та їхньою здатністю до прикріплення до культуральних чашок. Висновки. Нaдeкспресія CHI3L1, очевидно, має важливе значення в пухлиноутворунні і опоседковується активацією PI3K- і MAPK- сигнальних шляхів. Пухлини, спричинені ортотопічною імплантацією трансформованих клітин людини з нaдекспресованимCHI3L1 у мозок щурів, стають вірогідною мішенню для антиракової терапії. Ключові слова: хітиназа 3-подібний білок 1 (CHI3L1), пухлини гoлoвного мозку, MAP-кіназа, PI3-кіназа. Цель. Охарактеризовать иммортализованную клеточную линию 293 после стабильной трансфекции онкогена CHI3L1. Методы. Клетки 293, стабильно трансфецированные pcDNA3.1_CHI3L1, и клетки 293, стабильно трансфецированные pcDNA3.1 в качестве отрицательного контроля, использованы во всех экспериментах. Клоны 293_CHI3L1 и клетки 293_ pcDNA3.1 анализировали методами иммунофлюоресценции и конфокальной микроскопии. Клеточную пролиферацию определяли с помощью MTT, активацию и локализацию ERK1/2 и AKT анализировали с применением анти-фосфо-ERK- и анти-фосфо-AKT-антител. Специфическую активацию MAP- и PI3-киназ определяли денситометрическим анализом Вестерн-блот сигналов. Результаты. Полученные ре - зультаты демонстрируют умеренную способность CHI3L1 стимулировать клеточный рост и отражают скорее повышенную способность к прикреплению клеток, стабильно трансфецированных pcDNA3.1_CHI3L1 по сравнению с 293-клетками, транс - фецированными «пустым» вектором. ERK1/2 и AKT в клетках 293_CHI3L1 находятся в активированном состоянии. В этих клетках фосфорилированныe ERK1/2 локализованы как в цитоплазме, так и в ядре, в то время как AKT – только в цитоплазме. Клетки 293_CHI3L1 отличаются от клеток 293_pcDNA3.1 по морфологии и способности прикрепления к культуральным чашкам. Выводы. Сверхэкспрессия CHI3L1, очевидно, имеет важное значение в опухолеобразовании и опосредуется активацией PI3Kи MAPK-сигнальных путей. Опухоли, которые индуцируются ортотопической имплантацией трансформированных человеческих клеток со сверхэкспрессированным CHI3L1 в мозг крыс, мо - гут служить мишенью для антираковой терапии. Ключевые слова: хитиназа 3-подобный белок 1 (CHI3L1), опухоли гoлoвного мозга, MAP-киназа, PI3-киназа